Pharmacokinetics and pharmacodynamics of ticagrelor when treating non-ST elevation acute coronary syndromes. (June 2015) - Monitillo, Francesco; Iacoviello, Massimo; Caldarola, Pasquale; Valle, Roberto; Chiatto, Mario; Aspromonte, Nadia
<x xml:space="preserve">Abstract</x> Introduction: ADP-induced platelet activation via P2Y12 receptor plays a pivotal role in the pathophysiology of arterial thrombosis and acute coronary syndrome. The value of dual antiplatelet therapy with the addition of the thienopyridine clopidogrel to aspirin has been widely established. Prasugrel, another thienopyridine, has demonstrated more potent platelet inhibition and efficacy than clopidogrel, although this drug requires metabolic activation and is associated with increased risk of bleedings. Areas covered: In this article, we discuss the role of <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=ticagrelor&logicalOpe1=OR&field2=articletitle&text2=ticagrelor&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">ticagrelor in the management of non-ST elevation acute coronary syndromes treatment. We describe the unique pharmacokinetic and pharmacodynamic properties of this drug and the extensive data obtained by preclinical and Phase II and III clinical studies. Expert opinion: Current guidelines recommend ticagrelor, in addition to aspirin, for patients with non-ST-segment elevation acute coronary syndromes at moderate to high-risk regardless of initial therapeutic strategy. Benefit of ticagrelor, as regard mortality, may be related to off-target effects of the drug, especially those involving the metabolism of adenosine. Ticagrelor represents a cost-effective alternative in the spectrum of P2Y12 inhibitors; however, further studies are required to enable the physician to choose the most appropriate antiplatelet agent for each patient.